Global Land Grabbing and the Neo-Extractivism: A Post-Socialist Perspective - Petrović, Mina (Zbornik Instituta za kriminološka i sociološka istraživanja, 2023)
The paper analytically connects neo-extractivism, as the current development phase of capitalism, with the phenomenon of land grabbing, which refers to the importance of direct foreign investments in less developed countries aimed at acquiring land for the exploitation of ores and minerals, production of biofuel and food. Firstly, some relevant critical interpretations of land grabbing and neo-extractivism are presented, as well as the question of whether the observed territorialization of the resistance to the neo-extractivism increases mobilization potential or populist divisions in related social movements. Secondly, attention is drawn to the exposure of European post-socialist countries to these processes, including the experience of Serbia, and emphasizes that it is still a relatively neglected research topic in sociology.